Germ-line and somatic EPHA2 coding variants in lens aging and cataract - Bennett, Thomas M. (PLoS One, 2017)
Rare germ-line mutations in the coding regions of the human EPHA2 gene (EPHA2) have been associated with inherited forms of pediatric cataract, whereas, frequent, non-coding, single nucleotide variants (SNVs) have been associated with age-related cataract. Here we sought to determine if germ-line EPHA2 coding SNVs were associated with age-related cataract in a case-control DNA panel (> 50 years) and if somatic EPHA2 coding SNVs were associated with lens aging and/or cataract in a post-mortem lens DNA panel (> 48 years). Micro-fluidic PCR amplification followed by targeted amplicon (exon) next-generation (deep) sequencing of EPHA2 (17-exons) afforded high read-depth coverage (1000x) for > 82% of reads in the cataract case-control panel (161 cases, 64 controls) and > 70% of reads in the post-mortem lens panel (35 clear lens pairs, 22 cataract lens pairs). Novel and reference (known) missense SNVs in EPHA2 that were predicted in silico to be functionally damaging were found in both cases and controls from the age-related cataract panel at variant allele frequencies (VAFs) consistent with germ-line transmission (VAF > 20%). Similarly, both novel and reference missense SNVs in EPHA2 were found in the post-mortem lens panel at VAFs consistent with a somatic origin (VAF > 3%). The majority of SNVs found in the cataract case-control panel and post-mortem lens panel were transitions and many occurred at di-pyrimidine sites that are susceptible to ultraviolet (UV) radiation induced mutation. These data suggest that novel germ-line (blood) and somatic (lens) coding SNVs in EPHA2 that are predicted to be functionally deleterious occur in adults over 50 years of age. However, both types of EPHA2 coding variants were present at comparable levels in individuals with or without age-related cataract making simple genotype-phenotype correlations inconclusive.